Carrier-Free, Hyaluronic Acid-Modified Self-Assembled Doxorubicin, and Chlorin e6 Nanoparticles Enhance Combined Chemo- and Photodynamic Therapy in vivo - Lin B; Lin P; Zhang X; Liao Y; Yu Y; Xu X; Wang X (International Journal of Nanomedicine)
BeiBei Lin, Peizhen Lin, Xiaobi Zhang, Yingyi Liao, Yinfei Yu, Xuegu Xu, Xiaoling Wang State Key Laboratory of Ophthalmology, Optometry and Visual Science, National Clinical Research Center for Ocular Diseases, Eye Hospital, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Xuegu Xu; Xiaoling Wang, Tel +86-0577-8806-8864, Email xuexuegu@eye.ac.cn; ysgwxl@eye.ac.cnBackground: Developing carrier-free nanomedicines via self-assembly of two antitumor drug molecules is a potential strategy for enhancing the combination treatment of tumors. Similarly, conventional chemotherapy combined with photodynamic therapy may synergistically improve the antitumor effect while minimizing the adverse reactions associated with antitumor treatment. Hyaluronic acid (HA) can bind to overexpressed HA receptors on the tumor cell surface, increasing cell internalization and resulting in good tumor-targeting properties.Methods: Herein, we propose an easy and environmentally friendly approach for fabricating a novel formulation of carrier-free pure nanodrugs through self-assembly of the antitumor drug doxorubicin (DOX) and the photosensitizer chlorin e6 (Ce6), followed by sequential modification with HA to achieve simultaneous and targeted photodynamic therapy and chemotherapy.Results: The fabricated HA-DOX-Ce6 nanoparticles (NPs) exhibited enhanced drug loading and stability while possessing the properties of near-infrared fluorescence imaging, self-targeting drug delivery, and combined photodynamic therapy and chemotherapy.Conclusions: HA-DOX-Ce6 NPs, along with laser irradiation, effectively suppressed tumor development both in vitro and in vivo with minimal side effects. Overall, this biomaterial-based, carrier-free drug delivery system, in combination with cotargeted therapies, has shown potential for considerable improvements in treatment outcomes and patient prognosis.Keywords: carrier-free, self-assembly, hyaluronic acid, cancer targeting, chemotherapy, photodynamic therapy